Reading the Unconscious: A Psychoanalytical Study of Antoine de Saint Exupéry’s The Little Prince (1943) - Raza, Rubab (JELLL, 2024)
With the advent of the 21st century the “traditional boundaries” between different genres of literature have been blurred due to the innovative analytical and research approaches introduced by the contemporary scholars. Therefore besides looking at the entertaining side of the Children’s literature, modern-day researchers are also inclined to explore its hidden socio-cultural and psychological perspectives essential for the balanced spiritual and intellectual growth of a child. In this perspective The Little Prince (1943) by Antoine de Saint Exupéry can be considered an apt example of an apparently children’s novella but with a much deeper psychological thread to explore. The story follows the expeditions of a young prince who visits various planets, including Earth, to gain wisdom, and addresses the themes of loneliness, friendship, love, and loss. This particular Qualitative research is focused on the philosophical observations of the novella about life, adults, and human nature, and draws an inherent connection between an individual’s unconscious memories and his conscious understanding of the physical world around him. In order to comprehend this connection between human conscious and unconscious the research follows the theoretical framework proposed by Carl Jung and discussed by Hamida Bosmajian in Peter Hunt’s Understanding Children’s Literature (1999). Thus the fantasy world of The Little Prince has been taken as an allegory for the better understanding of the Jungian perspective related to the symbiotic relationship between the worldly wisdom and the latent unconscious memories and images of an individual. In this way man’s attempt to acquire conscious understanding of the physical world can also be considered a step towards the spiritual enlightenment of his unconscious. The research is significant because it voices out that spiritual and intellectual growth is a life-long progress which continues throughout life and one’s personal and communal experiences play an active part in this process, as one notices in the case of the little prince.